2009
DOI: 10.1128/mcb.01349-08
|View full text |Cite
|
Sign up to set email alerts
|

Sam68 Regulates a Set of Alternatively Spliced Exons during Neurogenesis

Abstract: Sam68 (Src-associated in mitosis, 68 kDa) is a KH domain RNA binding protein implicated in a variety of cellular processes, including alternative pre-mRNA splicing, but its functions are not well understood. Using RNA interference knockdown of Sam68 expression and splicing-sensitive microarrays, we identified a set of alternative exons whose splicing depends on Sam68. Detailed analysis of one newly identified target exon in epsilon sarcoglycan (Sgce) showed that both RNA elements distributed across the adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 64 publications
4
123
0
Order By: Relevance
“…[14][15][16] An example of RBP that is upregulated in several human tumors is SAM68 (Src-associated in mitosis of 68 kDa), a member of the STAR (Signal Transduction Activator of RNA metabolism) family of RBPs. 17 SAM68 is involved in regulating several aspects of RNA processing, such as transcription, [18][19][20][21] AS [22][23][24][25] and translation of cellular mRNAs. [26][27][28] Moreover, SAM68 displays pro-oncogenic functions and is frequently upregulated in human cancer types, 17 including prostate cancer (PCa), wherein it supports cell proliferation and survival to genotoxic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] An example of RBP that is upregulated in several human tumors is SAM68 (Src-associated in mitosis of 68 kDa), a member of the STAR (Signal Transduction Activator of RNA metabolism) family of RBPs. 17 SAM68 is involved in regulating several aspects of RNA processing, such as transcription, [18][19][20][21] AS [22][23][24][25] and translation of cellular mRNAs. [26][27][28] Moreover, SAM68 displays pro-oncogenic functions and is frequently upregulated in human cancer types, 17 including prostate cancer (PCa), wherein it supports cell proliferation and survival to genotoxic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of this element promoted the skipping of Rps6kb1 exons 6a, 6b, and 6c, thus preventing the expression of Rps6kb1-002. Sam68 is an established regulator of alternative splicing, and it is known to function by directly associating with A/U-rich elements near 5= splice sites (5,10,12,16). The Rps6kb1 intron 6 UAAU UAAA bipartite sequence is recognized by Sam68 with relatively high affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Sam68 regulates the epithelial-to-mesenchymal transition by decreasing the presence of an alternative serine/arginine-rich splicing factor 1 gene (Srsf1) transcript degraded by nonsense-mediated mRNA decay (9). Sam68 has been shown to regulate alternative splicing of mRNAs during neurogenesis (10) and in cerebellar neurons (11). Stimulation of cerebellar neurons using the glutamate receptor agonist kainic acid was dramatically attenuated without Sam68, indicating that Sam68 is required for activity-dependent alternative splicing of Nrxn1 in vivo (11).…”
mentioning
confidence: 99%
“…12 In addition, it was demonstrated that Sam68 was required for maintaining patterns of splicing even after differentiation had occurred. As Sam68 knockout mice exhibit defects in basal motor coordination, 4 the alterations in splicing patterns may partly contribute to this defect.…”
Section: Sam68 and Alternative Splicingmentioning
confidence: 99%